Kinetics of Fly Ash Geopolymerization using Semi Quantitative Fourier-Transform Infrared Spectroscopy (FTIR); Corr Data. (May 2019) - Murti Petrus, Himawan Tri Bayu; Adelizar, Arie Satya; Widiyatmoko, Achmad; Olvianas, Muhammad; Suprapta, Wisnu; Perdana, Indra; Prasetya, Agus; Astuti, Widi
Abstract: Fly ash utilization is very urgent to be conducted alas contaminating the environment. One of the promising utilizations is geopolymer formation for material construction. In this study, geopolymer formation was studied using fly ash from PLTU Tanjung Jati Jepara. This study included kinetics prediction using solid state isoconversion kinetics that has been developed based on nucleation, geometric contraction, and diffusion models. Semi quantitative FTIR analysis (corr) has been applied to predict the kinetics of the fly ash geopolymerization in curing temperature of 30о and 90°C. In order to be able to verify the kinetics model time series data were taken in interval of 1, 3, 5, 14, 21, and 28 days. It is the diffusion model that represents the fly ash geopolymerization with R 2 of 0.9437.